Stress transfer and matrix-cohesive fracture mechanism in microfibrillated cellulose-gelatin nanocomposite films. (1st September 2018) - Quero, Franck; Padilla, Cristina; Campos, Vanessa; Luengo, Jorge; Caballero, Leonardo; Melo, Francisco; Li, Qiang; Eichhorn, Stephen J.; Enrione, Javier
Graphical abstract: Highlights: Stress transfer is quantified for the first time in microfibrillated cellulose-gelatin nanocomposite films by Raman spectroscopy. Stress is more efficiently transferred from bovine gelatin to microfibrillated cellulose when compared to salmon gelatin. Matrix-cohesive fracture mechanism is predominant in this form of microfibrillated cellulose-gelatin nanocomposite films. Improved mechanical performance (both strength and flexibility) is obtained when salmon gelatin is used as a matrix material. Abstract: Microfibrillated cellulose (MFC) obtained from eucalyptus was embedded in gelatin from two sources; namely bovine and salmon gelatin. Raman spectroscopy revealed that stress is transferred more efficiently from bovine gelatin to the MFC when compared to salmon gelatin. Young's modulus, tensile strength, strain at failure and work of fracture of the nanocomposite films were improved by ∼67, 131, 43 y 243% respectively when using salmon gelatin as matrix material instead of bovine gelatin. Imaging of the tensile fracture surface of the MFC-gelatin nanocomposites revealed that crack formation occurs predominantly within bovine and salmon gelatin matrices rather than within the MFC or at the MFC/gelatin interface. This suggests that the mechanical failure mechanism in these nanocomposite materials is predominantly governed by a matrix-cohesive fracture mechanism. Both strength and flexibility are desirable properties for composite coatings made from gelatin-based materials, and so the findings of this study could assist in their utilization in the food and pharmaceutical industry.